PENGEMBANGAN MEDIA KOMIK BERBASIS KEARIFAN LOKAL SUMATERA UTARA PADA MATA PELAJARAN IPAS MATERI DAERAHKU DAN KEKAYAAN ALAMNYA DI KELAS IV SD - Try Ayunda Tasya; Nurmairina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to: (1) produce comic media products based on the local wisdom of North Sumatra in the science and science subject of my region and its natural riches in class IV elementary school, (2) test the feasibility level of comic media based on the local wisdom of North Sumatra in the science and science subject of my region. and its natural riches in fourth grade elementary school. This research is a type of Research and Development (R&D) research with 4D research procedures by Thiagarajan which includes four stages, including: 1) Define Stage, 2) Design Stage, 3) Development Stage, 4) Disseminate Stage (Dissemination). The subjects in this research were media expert validators, material experts, learning experts and fourth grade elementary school students. The research instrument used in data collection was a questionnaire. The results of this research show that Comic Media Based on Local Wisdom of North Sumatra in the Science and Science Subject Subject My Region and Its Natural Resources in Class IV Elementary School is "Very Feasible" with details of the feasibility percentage given by media experts of 94.28% with the criteria "Very Feasible", material experts were 95% with the criteria "Very Eligible", learning experts were 96% with the criteria "Very Eligible". Therefore, it can be concluded that Comic Media Based on Local Wisdom of North Sumatra in Science and Science Subjects, My Region Material and Its Natural Wealth in Class IV Elementary School is “Very Appropriate" to be used by students during the learning process